Security in the South American political cooperation agenda - Wagner, Allan (2016)
The strengthening of peace and security is considered in this article as one of the main objectives of the Common International Foreign Policy of the Andean Community of Nations (CAN). This article presents an analysis of how various documents have handled the topic of regional security including, for example, the Brasilia Declaration, in which South American presidents agreed upon creating a "peace zone" in South America. From a study of the existing instruments of both CAN and MERCOSUR, the author explores the possibilities of establishing such "peace zones', and what requisites would be necessary in order to pursue an agenda in that direction.